Technopreneur blogging information technology knowledge and business - Gamboa, Randy S. (Southeastern Philippines Journal of Research and Development, 2014)
This research is about how Information Technology (IT) knowledge sharing and business are incorporated to attain successful techno blogging approach. The research was conducted to (1) identify the blogging platforms and blog ad sites available to the bloggers, (2) determine the different procedures established by blog advertisement sites in blog monetization, (3) identify the IT topics commonly shared in blogs that contribute to the effective IT knowledge sharing and (4) determine the different effective ways in attaining successful incorporation of IT knowledge and business. Different IT blogger from Mindanao and IT students and professors from the (1) University of the Immaculate Concepcion, (2) University of Mindanao (3) Ateneo de Davao University and (4) University of Southeastern Philippines were the respondents of the study. The following blogging platforms were identified (a) Blogger (blogspot.com), (b) Blogsome, (c) Wordpress.com and (d) Wordpress.org. Different advertisement sites were likewise identified and these are (a) Adsense, (b) Blogsvertise (c) Sponsored Reviews and (d) Bloggerwave. The common IT topics were talk about software, gadgets and Free and Open Source Software (FOSS). The relationship between the frequency and effectiveness of these topics were also analyzed and interpreted. Lastly, the different ways in attaining successful technopreneur blogging were identified and the level of effectiveness in each of theses was also measured. Writing sensible contents in blog posts was proven to be the most effective way in technopreneur blogging.